The Kalevala and Finland’s Atlantean Past: Willie Angervo’s Esoteric History - Korpi, Ossi (Donner-instituutti, 2025)
Nationalistic interpretations of history were prevalent in Finland until the Second World War. A unifying past for Finns was sought in antiquity, often influenced by interpretations of the Kalevala, regarded as the Finnish national epic. The Kalevala also inspired writers in the Theosophical Society, who promoted various alternative views of humanity’s past. In this article, I analyse the late 1930s writings of Wilho “Willie” Angervo (1875–1938), a medical colonel and author who had a central role in the Finnish Order of the Star in the East and the Theosophical Society in his time. Inspired by the Kalevala, Angervo traced the origins of the Finns to the lost continent of Atlantis and aimed to revitalize the pre-Christian “faith of the forefathers”. Dialogical narrative analysis is employed to explore how Angervo portrayed the Finns’ past, combining Theosophical and nationalistic ideas to construct an ideal Finnishness. I argue that Angervo utilized the Theosophical timeline and concepts to construct a spiritually oriented national narrative for the Finns that would surpass any political quarrels and challenge both the Church and more military-oriented nationalism.